2013
DOI: 10.1016/j.jcyt.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Defining “poor mobilizer” in pediatric patients who need an autologous peripheral blood progenitor cell transplantation

Abstract: The definition of poor mobilizers is not clear in pediatric patients undergoing autologous peripheral blood hematopoietic progenitor cell (HPC) mobilization. Most studies conducted in children define those variables related to the collection of HPC after leukapheresis, but the information regarding exclusively the mobilization process is scarce. In our experience, most children (92.2%) reach the target CD34(+) cell dose for autologous peripheral blood progenitor cell transplantation if CD34(+) cell count was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…A study of 179 patients undergoing PBSC apheresis showed that 92% of patients can reach their target CD34 + dose if the pre‐apheresis PB‐CD34 + count was >10. There was no difference found for those with PB‐CD34 + > 20 vs 11‐20 in the study . Similarly, in our study all successful collections occurred in patients with a PB‐CD34 + > 10; however, among the four failed collections with a PB‐CD34 + < 20, all were between 10 and 20.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…A study of 179 patients undergoing PBSC apheresis showed that 92% of patients can reach their target CD34 + dose if the pre‐apheresis PB‐CD34 + count was >10. There was no difference found for those with PB‐CD34 + > 20 vs 11‐20 in the study . Similarly, in our study all successful collections occurred in patients with a PB‐CD34 + > 10; however, among the four failed collections with a PB‐CD34 + < 20, all were between 10 and 20.…”
Section: Discussionsupporting
confidence: 56%
“…Factors that predict poor mobilization include underlying disease, involvement of bone marrow by metastatic disease and relapse . Treatment related factors include multiple lines of previous therapy, in particular marrow toxic agents such as purine analogs, mid‐cycle vincristine chemotherapy given prior to apheresis, and previous exposure to radiation . Factors related to the mobilization regimen include a higher yield with chemotherapy + G‐CSF than with G‐CSF alone and total G‐CSF dose .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have been published exploring poor mobilization in pediatric patients and therefore there is no current consensus threshold for poor mobilization in this patient group. In a single retrospective study of pediatric patients, who received a mobilization regime consisting of G-CSF for 4 days, prior to collection of CD34+ cells, [8] no differences were observed in the numbers of patients reaching the target cell dose (2 × 10 6 cells/µL) for autologous PB progenitor cell transplantation in patients with baseline PB CD34+ cells counts of >20 cells/µL compared with those with baseline CD34+ cells counts of 11-20 cells/µL [8]. Of 26 pediatric patients with a PB CD34+ cell count of ≤10 cell/µL, 18 underwent hematopoietic progenitor cell collection, two reached the target CD34+ cell dose after one apheresis, and 16 failed to reach the target [8].…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF has been reported to fail to mobilize a sufficient number of PBSCs for transplantation in some elderly patients and especially in patients with a history of chemotherapy or radiotherapy [69, 84, 85, 93, 97, 103]. Other factors associated with poor mobilization include a low platelet count immediately before mobilization [85], baseline thrombocytopenia [85, 92], diabetes [104], and a low TNF- α level [105].…”
Section: Therapeutic Outcomes: Hspc Mobilizationmentioning
confidence: 99%